Structure and dynamics of catabolite gene activator protein by molecular modeling and simulations - Fas, Ayşe Burcu Aykaç. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
The activities of proteins are regulated by interactions with other molecules through various types of local to global motions. Such internal motions may occur at different time scales and involve complex correlations between the atomic motions. To this end, it is of importance to have the knowledge of different conformational states of a system and to search for the conformational transitions between these states. In the present thesis, the main focus has been to investigate the structural and dynamic features of the plausible apo forms of catabolite activator protein (CAP) in solution, whose crystal structure has not been resolved until now, by modeling and molecular simulations. Molecular dynamics (MD) simulations have been run and analyzed for the unbound monomer and the dimer structures of CAP. Besides the direct conventional analysis of the large amount of the conformations generated by MD simulations, these conformations have further been processed by clustering. The cluster best members have been analyzed with respect to their structural and dynamic peculiarities. The elastic network models are also used for the analysis of the cluster best members. The dynamic fluctuations, the conservation and variation of the fluctuations from one cluster to another have been analyzed. Comparison with the results from the direct analysis of the MD trajectories have been carried out. The combined analysis of the results by various means suggest that the monomeric structure could be a plausible structure for the apo state. The helicity content, the existence of the salt bridges, the shift of a hinge in the DNA binding domain agree with the experimental observations in the apo state, whereas the stabilization of the two domains, cAMP and DNA binding, and their association is enhanced by the DNA binding region upon dimerization. The predicted fluctuations for the cluster best members by elastic network models agree with the conformational space spanned by the cluster best members. The results in general provide evidence for the preexistence of the conformations of the monomer, in the dimer unbound state.
Keywords: Proteins -- Analysis.; Proteins -- Structure.